ANALISIS PENGGUNAAN UANG ELEKTRONIK TERHADAP PERTUMBUHAN EKONOMI: STUDI EMPIRIS INDONESIA TAHUN 2014-2021 - Febitania, Nabila Zakia; Agus Suman (Journal of Development Economic and Social Studies, 2024)
The use of modern technology is growing rapidly, with innovation leading to the increasing replacement of cash transactions by electronic payments. This trend is reflected in the value of electronic money transactions which continues to increase, reaching IDR 786.35 trillion in 2021. Thus, the aim of this research is to assess how Indonesia's economic growth is influenced by the use of electronic payment systems. The study approach examines possible short-term and long-term relationships between electronic money, money supply, interest rates, inflation and economic growth using the Vector Error Correction Model (VECM). Using documentation techniques, data on GDP, money supply, electronic money transactions, interest rates and inflation were collected from Bank Indonesia and the Central Statistics Agency between 2014 and 2021. According to research, there is a short-term relationship between economic growth and the use of electronic money. However, as time goes by, economic growth is only influenced by the positive relationship between inflation and the money supply. These results are intended to provide insight for decision makers in Indonesia to continue to innovate in the development of electronic money to support sustainable economic growth.